Nursing Approaches to Pain Management in Labor for Mothers in Hospitals Across Asia - Rejeki, Sri; Khayati, Nikmatul (South East Asia Nursing Research, 2023)
Effective pain management during childbirth is crucial for ensuring the well-being of both mother and child. In Asia, diverse approaches to managing labor pain are applied in hospital settings, combining both pharmacological and non-pharmacological strategies. Cultural values, resource availability, and healthcare systems significantly influence the approaches used. This review explores nursing approaches to labor pain management across different countries in Asia, highlighting common methods, their effectiveness, and the challenges encountered.